Against War - Erasmus, Desiderius (Auckland : The Floating Press, 2012)
Dutch thinker and theologian Desiderius Erasmus played a key role in the development of humanism during the Renaissance and early modern periods. In Against War, Erasmus mounts a stunningly lucid and detailed argument against armed combat on humanistic grounds. It's a must-read for anyone who has strong feelings about the moral and ethical dimensions of militaristic undertakings.
Title; Contents; Introduction; Against War
Description based upon print version of record.
Keywords: Erasmus, Desiderius -- 1536.; Pacifism; War; Political Science; Religion; War; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books